2023
DOI: 10.3389/fpsyt.2023.1119142
|View full text |Cite
|
Sign up to set email alerts
|

The importance of comprehensive support based on the three pillars of exercise, nutrition, and sleep for improving core symptoms of autism spectrum disorders

Abstract: Autism spectrum disorder (ASD) is classified as a neurodevelopmental disorder. The Diagnostic and Statistical Manual of Mental Disorders (DSM)-V, which first described ASD, lists persistent deficits in social communication and interrelationships, as well as limited and recurrent modes of behavior, interests, and activities as diagnostic items. Until recently, understanding the pathophysiology of ASD has been mostly from a neurophysiological perspective, and interventions have been mostly behavioral and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Of the 40 articles analyzed, all but one was published after 2000, of which 36 (90%) were published after 2010. Many intervention studies with physical activity/exercise for ASD and AD/HD have been published in recent years, suggesting that this field has been recently pioneered (Yano and Hosokawa, 2023). It is now known that physical activity/exercise has a variety of benefits, including low cost and a small risk of side effects, in addition to its effectiveness in improving the core symptoms of neurodevelopmental disorders (Bremer et al, 2016).…”
Section: Study Areas and Publication Date (1) Countries And Areasmentioning
confidence: 99%
“…Of the 40 articles analyzed, all but one was published after 2000, of which 36 (90%) were published after 2010. Many intervention studies with physical activity/exercise for ASD and AD/HD have been published in recent years, suggesting that this field has been recently pioneered (Yano and Hosokawa, 2023). It is now known that physical activity/exercise has a variety of benefits, including low cost and a small risk of side effects, in addition to its effectiveness in improving the core symptoms of neurodevelopmental disorders (Bremer et al, 2016).…”
Section: Study Areas and Publication Date (1) Countries And Areasmentioning
confidence: 99%
“…Advance Publication by J-STAGE Published online February 14, 2024 Therefore, recent years have seen a focus on physical activity/exercise-based therapies with low cost and no risk of side effects (Bremer et al, 2016;Healy et al, 2018). We comprehensively reviewed intervention studies using aerobic exercise such as running, swimming, and aquatic exercise (Battaglia et al, 2019), sports such as basketball (Cai et al, 2020), and martial arts such as Judo and Karate, and reported that these have beneficial effects for ASD (Yano and Hosokawa, 2023). However, there are few systematic reviews focusing on individualized exercise programs (e.g., Martin and Dillenburger., 2019;Mortimer et al, 2014), and summarized information leading to more effective interventions is limited.…”
Section: Introductionmentioning
confidence: 99%